2019
DOI: 10.1038/s41438-019-0218-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional identification of lncRNAs in sweet cherry (Prunus avium) pollen tubes via transcriptome analysis using single-molecule long-read sequencing

Abstract: Sweet cherry (Prunus avium) is a popular fruit with high nutritional value and excellent flavor. Although pollen plays an important role in the double fertilization and subsequent fruit production of this species, little is known about its pollen tube transcriptome. In this study, we identified 16,409 transcripts using single-molecule sequencing. After filtering 292 transposable elements, we conducted further analyses including mRNA classification, gene function prediction, alternative splicing (AS) analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Recently, Li et al. (2019) predicted 2043 AS events in sweet cherry pollen tubes using single‐molecule long‐read sequencing. They suggested that RI was the main group, comprising 37.6% of the AS events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Li et al. (2019) predicted 2043 AS events in sweet cherry pollen tubes using single‐molecule long‐read sequencing. They suggested that RI was the main group, comprising 37.6% of the AS events.…”
Section: Resultsmentioning
confidence: 99%
“…A high abundance of ES events has been previously reported in peach (Prunus persica; 43%), in contrast to reports on annual plant species such as Arabidopsis, rice (Oryza sativa), maize (Zea mays), and others, where 30% of AS events represent RI (Barbazuk et al, 2008;Marquez et al, 2012;Zhang et al, 2020). Recently, Li et al (2019) predicted 2043 AS events in sweet cherry pollen tubes using single-molecule long-read sequencing. They suggested that RI was the main group, comprising 37.6% of the AS events.…”
Section: Alternative Splicing Eventsmentioning
confidence: 94%
“…In addition, some lncRNAs interact with microRNAs (miRNAs), serving as miRNA precursors or competing endogenous RNAs (ceRNAs) to serve as decoys for specific miRNAs, thus protecting the target mRNAs from repression [29][30][31][32] . In recent years, several studies have indicated that lncRNAs play important roles in various biological processes in plants, including roles in organ development, nutrient metabolism, male sterility, and plant immunity [33][34][35][36][37] . In particular, lncRNAs are considered essential regulators of the response to biotic and abiotic stresses in plants 30,[38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
“…In plants, although a large number of lncRNAs have been predicted in different biological contexts in quite a few plant species ( Ding et al, 2012 ; Li et al, 2014 ; Shuai et al, 2014 ; Zhang et al, 2014 ; Hao et al, 2015 ), only a handful of plant lncRNAs have been experimentally characterized. Several lines of evidence have shown that these lncRNAs play critical roles in regulating the expression of genes involved in biotic or abiotic stress responses ( Franco-Zorrilla et al, 2007 ; Di et al, 2014 ; Zhu et al, 2014 ; Seo et al, 2017 ; Song et al, 2021 ), vegetative growth ( Ariel et al, 2014 ), fruit development ( Bai et al, 2019 ), reproductive processes ( Ding et al, 2012 ; Zhang et al, 2014 ; Li et al, 2019 ), and flowering time ( Swiezewski et al, 2009 ; Heo and Sung, 2011 ; Kim and Sung, 2017 ) in plant life cycle. In Arabidopsis thaliana , about 6,480 lncRNAs were identified using genome-wide screening of 200 transcriptome data with tissue-specific expression profiles ( Liu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%